Peningkatan Hasil Belajar Menulis Teks Deskriptif melalui Metode Team Game Tournament di Madrasah Aliyah Negeri 3 Sleman - Puji Astuti, Indarti (Jurnal Pendidikan Madrasah, 2024)
This study aims to determine the application of the Team Games Tournament learning model in improving learning outcomes in writing English descriptive texts. This study used a class action research method which was carried out in 2 cycles, each cycle consisted of 2 meetings. The subjects of the study were students of class X-C MAN 3 Sleman in the first semester of the 2023/2024 academic year. The results of this study showed that there was an increase in English learning outcomes of X-C grade students, which was shown by: (1) the average learning outcomes in cycle I of 72.74 increased to 79.72 in cycle II; (2) learning completeness in cycle I of 62.5% (20 students) increased to 75% (24 students) in cycle II of a total of 32 students. This learning activity shows that the Team Games Tournament cooperative learning model can be applied to materials related to writing descriptive texts.